Settling of particles in the upper 100 m of the ocean detected with autonomous profiling floats off California. (May 2015) - Jackson, George A.; Checkley, David M.; Dagg, Michael
Abstract: We have deployed an autonomous profiling float, the SOLOPC, to sample the concentration of particles larger than 100 μm off the California coast at approximately hourly intervals down to at least 100 m for periods as long as 12 d. We used the data to estimate total aggregate concentrations hourly at 2-m depth intervals, studying the dynamics of particle sedimentation in this difficult-to-sample region. We find that even over time scales of a week, sedimentation is highly variable, with detectable sedimentation events on about one quarter of the days. Most of these observations were along the southwest coast of the United States, a region known for its coastal upwelling and not necessarily representative of more oligotrophic regions. The aggregate settling rates that we estimate, on the order of 50 m d −1, are consistent with in situ measurements and with rates calculated from coagulation models. The time interval between observations and their vertical resolution constrain the velocities that can be measured. To capture particle settling with velocities less than the 100 m d −1 that is usually reported for near surface aggregates requires a sampling interval no more than about 0.25 d with a 2 m vertical resolution. This technique provides a powerful new tool to study the dynamics of particles and their sedimentation near the ocean surface, where export starts. Highlights: Using SOLOPC profilers, we sampled aggregate distributions ~hourly 12 times. The time evolution of aggregate concentrations showed particle sinking events. Sinking events were detectable in about 1/4 of the days. Sinking velocities were typically about 50 m d −1 . The methodology is useful for profiling floats and gliders.